1998
DOI: 10.2135/cropsci1998.0011183x003800030034x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Baking and Noodle Quality in Hard White Spring Wheat

Abstract: There is growing interest in the use of hard white wheat (Triticum aestivum L.) for both the production of oriental noodles and making bread. It would be desirable if new hard white wheat cultivars produced flour suitable for both purposes. Our objective was to address the feasibility of developing such dual purpose white wheats. We tested several hard white spring wheat lines grown in three locations in Montana for quality characteristics associated with both end‐use products. The hard white spring wheat line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 0 publications
3
57
1
Order By: Relevance
“…In the case of WSN and YAN, variations in gluten properties (as indicated by farinograph parameters or SDSsedimentation volume) were found to have significant effects on noodle firmness, elasticity, and smoothness (Miskelly, 1981;Huang & Morrison, 1988;Konik et al, 1994;Ross et al, 1997;Lang et al, 1998). In contrast, variations in starch properties were been found to play a major role in noodle softness and viscoelastic properties (Crosbie, 1991;Crosbie et al, 1992Crosbie et al, , 1999Crosbie & Lambe, 1993;Yun et al, 1996;Toyokawa et al, 1989;McCormick et al, 1991;Konik & Miskelly, 1992;Konik et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of WSN and YAN, variations in gluten properties (as indicated by farinograph parameters or SDSsedimentation volume) were found to have significant effects on noodle firmness, elasticity, and smoothness (Miskelly, 1981;Huang & Morrison, 1988;Konik et al, 1994;Ross et al, 1997;Lang et al, 1998). In contrast, variations in starch properties were been found to play a major role in noodle softness and viscoelastic properties (Crosbie, 1991;Crosbie et al, 1992Crosbie et al, , 1999Crosbie & Lambe, 1993;Yun et al, 1996;Toyokawa et al, 1989;McCormick et al, 1991;Konik & Miskelly, 1992;Konik et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although some knowledge has been gained regarding wheat quality requirements for DWCN, much more work is needed to define clearly DWCN quality criteria, which remain largely undefined in the 10 diverse agro-ecological zones where Chinese wheat is grown (He, 1999). Lang et al (1998) demonstrated the potential difficulty of developing high protein hard wheat for semiarid environments, that are suitable for both bread and Asian noodle products. Although cultivars with acceptable bread and Chinese noodle quality have been identified, the negative effect of very high protein content on colour was confirmed by Habernicht et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple researchers have investigated the ideal combination of starch and protein characteristics necessary to create a HW wheat cultivar with dual-purpose quality; however, this relationship has not been firmly established (Lang et al 1998;Davies and Berzonsky 2003). A dual-purpose, or dual-use, HW wheat variety could be used to produce both high-quality pan bread and Asian noodles if it had desirable quality attributes for both end-product types.…”
Section: Dual-purpose Hard White Wheatmentioning
confidence: 99%
“…Grain yields of HW wheat often equal or exceed those of HRW or HRS wheat (Upadhyay et al 1984;Matus-Cádiz et al 2003). The bread-making qualities of HW wheat also are comparable to those of HRS wheat (Lang et al 1998). When milled to a common color standard, flour extraction rates of HW wheat are typically 1-3% higher than those of HRS wheat (Boland and Dhuyvetter 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation